LA CYBERCRIMINALITE A ABAIDJAN, UN PHENOMENE DE MODE OU UNE NOUVELLE GUERRE CONTRE LES FINANCES EN COTE D’IVOIRE? - Denis, Gueu (European Scientific Journal, ESJ, 2013)
The evolution of technology gave to the whole humanity a glimmer of hope because it makes easy the realization of works. Thus, transforming the world into one planetary village, the data processing tool becomes today essential in training and information. But it is not all the time success nor profits with the computers especially as one knows the nuisances that they create in finance and economic field. In Côte d’Ivoire, at present, the concept of cybercafé and that of the Internet are mixed up with robbery, swindling and criminality. The phenomenon so much became extensive and we wonder if it is not another way of war against Ivorian finances and economy. The authors of that practice are not inevitably foreigners because Ivorian youth are strongly involved in nowadays. It is necessary to act quickly in order to stop the misfortune of several people swindled all the time. That must pass by a sensitizing and common sub-regional fight against that phenomenon.